The Wisdom Innovation Model - Adjusting New Insights and Hosting New Perspectives to Human Augmented Reality - Dias, Albertina (2011)
In this paper, the process of constant innovation is analyzed comparing with the various economic eras that humanity has come through and even with the level of countries’ development. While technology enables the possible application of knowledge, the level of expertise may be evaluated by the effective outcomes. In this perspective, analyzing the concept of multimedia interactive books and its impact on learning, suggests the importance or need for emotional and knowledge management in a productive way instead of a reproductive type of learning. The aim of this paper is to present the findings of a Delphi research on the challenges of bringing new possible business models, economically efficient and socially effective when exploring new media tools for enhanced learning based on the technology of augmented reality and to adjust new insights and host new perspectives to the forthcoming human augmented reality.